Prevalence and associations for use of a traditional medicine provider in the SAMINOR 1 Survey: a population-based study on Health and Living Conditions in Regions with Sami and Norwegian Populations. - Kristoffersen, Agnete Egilsdatter; Stub, Trine; Melhus, Marita; Broderstad, Ann Ragnhild (BMC Complementary and Alternative Medicine, 2017)
Source at https://dx.doi.org/10.1186%2Fs12906-017-2037-0 BACKGROUND: In Northern Norway, traditional medicine (TM) is shaped by both Christianity and traditional Sami nature worship. The healing rituals may include prayer and the use of tools such as moss, water, stones, wool and soil. Examples of TM modalities offered is cupping, blood-stemming, laying on of hands, healing prayers, and rituals. The purpose of this study was to investigate the prevalence of the use of TM in areas with predominantly Sami and Norwegian populations, and the influence of ethnicity, geography, gender, age, education, household income, religiosity and self-reported health on such use. METHODS: The study is based on data collected in the first SAMINOR Survey (SAMINOR 1) conducted in 2003/2004, including three self-administered questionnaires, clinical measures, and blood analyses. Data was collected in 24 municipalities in Norway known to have a substantial population of Sami. All residents aged 30 and 36-78/79 years in the predefined regions were invited regardless of ethnic background (N = 27,987). Of these, 16,865 (60.3%) accepted to participate and gave their consent to medical research. RESULTS: Of the 16,544 people responding to the question about TM use, 2276 (13.8%) reported to have used TM once or more during their lifetime. The most outstanding characteristic of the TM users was the affiliation to the Laestadian church, where 34.3% (n = 273) reported such use, followed by an inner Finnmark residence (31.1%, n = 481) and a Sami ethnicity (25.7%, n = 1014). Women were slightly more likely to use TM compared to men (15.9% and 11.5% accordingly, p < 0.001), and the TM users were slightly younger than the non-TM users (mean age 52.3 versus 54.3 years, p < 0.001). The TM users also had lower income (p < 0.001) than the non-TM users. We found no significant differences between the TM users and the non-TM users concerning years of education, and whether the participants were living with a spouse/partner or not. CONCLUSION: ...